Tthe competitiveness of the future specialist as an indicator of the quality of university training. (Journal of Educational Sciences, 2016)
The article is devoted to the problems of competitiveness of the future specialist as an indicator of the quality of University training. One of the characteristic features of the concept of competence of the specialist is to enhance the role of the individual in social transformation and upgrading its capability to understand the dynamics of the processes of development and the impact on their progress. These requirements of professional competence are determined by the educational policies of the state.
Keywords: higher education; the educational programme; the competitiveness of education; competitiveness specialist; designing educational programs